A Theoretical Study of Tunable Brillouin Lasers Based on a Diamond Suspended Waveguide - Wang, Wuyue; Yu, Yu; Bai, Zhenxu; Li, Yunfei; Wang, Gong; Li, Kai; Song, Changyu; Wang, Zhiyong; Li, Sensen; Li, Yuhai; Liu, Tongyu; Yan, Xiusheng; et al. (Frontiers in Physics, 2022)
A new type of hybrid waveguide structure is designed, which realizes independent control of phonon mode and optomechanical driving force, thereby generating customizable Brillouin coupling over a very wide bandwidth. The Brillouin gain reached 4400 W-1m-1, and the phonon nonlinear tunability from 1 - 95 GHz was realized. This hybrid waveguide width tuning scheme can realize photon-phonon conversion based on the Brillouin nonlinear effect and can guide and manipulate the phonons emitted by Brillouin on the chip. Therefore, this technique provides the opportunity to generate microwave sources using the on-chip Brillouin photoacoustic coupling mechanism new possibility.